Evaluation of Specialization Preferences of Faculty of Dentistry Students - Nimet Ünlü; Atiye Tuğba Kuzgun Türkmen; Merve Gürses (European Annals of Dental Sciences)
Purpose: The aim of this study is to evaluate the post-graduation specialty education preferences of 3rd and 5th year dentistry students and the factors that motivate these preferences.Materials and Methods: This survey was applied to students of Selçuk University Faculty of Dentistry. A total of 207 students, 104 3rd grade and 103 5th grade students, participated in the study. Two different response types were used in the study: multiple choice and linear scale (1=strongly disagree, 2=disagree, 3=undecided, 4=agree, 5=strongly agree). A survey form was applied to the students via Google Forms.Results: While 3rd graders are mostly undecided about whether their undergraduate education should focus on DSE (48.1%), 5th graders think that undergraduate education (62.1%) is not aimed at DSE. In both grades, the rate of those who find it necessary to attend private teaching institutions is high. When choosing a department, 3rd-grade students (29.8%) mostly prefer Orthodontics; 5th graders (32%) chose Oral and Maxillofacial Surgery. While the 5th-grade students said they would prefer a faculty different from their own for specialization training, most 3rd-grade students were undecided. However, both grades stated that the department was more effective in determining their training specialty preferences than the city and university.Conclusion: Clinical internship training has an essential place in post-graduation career planning. Department preferences of 3rd and 5th-grade students in their specialization education differ. For both the 3rd and 5th grades, the department was more effective in determining their specialty training preferences than the city and university.